Mixed-sex offspring produced via cryptic parthenogenesis in a lizard - Kratochvíl, Lukáš; Vukić, Jasna; Červenka, Jan; Kubička, Lukáš; Johnson Pokorná, Martina; Kukačková, Dominika; Rovatsos, Michail; Piálek, Lubomír (Molecular ecology, 2020)
Facultative parthenogenesis in vertebrates is believed to be exceptional, and wherever documented, it always led to single-sex progeny with genome-wide homozygosity. We report the first challenge to this paradigm: frequent facultative parthenogenesis in the previously assumed sexually reproducing tropical night lizard Lepidophyma smithii results in offspring of both sexes and preserves heterozygosity in many loci polymorphic in their mothers. Moreover, we documented a mixture of sexually and parthenogenetically produced progeny in a single clutch, which documents how cryptic a facultative parthenogenesis can be. Next, we show that in the studied species, 1) parthenogenetically produced females can further reproduce parthenogenetically, 2) a sexually produced female can reproduce parthenogenetically, 3) a parthenogenetically produced female can reproduce sexually, and 4) a parthenogenetically produced male is fully fertile. We suggest that facultative parthenogenesis should be considered even in vertebrates with frequent males and genetically variable, heterozygous offspring.
Keywords: partenogeneze; reptiles; ddRAD sequencing; Homozygote; ještěři; reproduction; Female; zvířata; homozygot; vertebrates; sexual dimorphism; ženské pohlaví; Male; Heterozygote; Lizards; Animals; heterozygot; facultative parthenogenesis; mužské pohlaví; Parthenogenesis